Ultrasound and shock-wave stimulation to promote axonal regeneration following nerve surgery: a systematic review and meta-analysis of preclinical studies - Däschler, Simeon C.; Harhaus-Wähner, Leila (Scientific reports, 2018)
Limited regeneration after nerve injury often leads to delayed or incomplete reinnervation and consequently insufficient muscle function. Following nerve surgery, application of low-intensity ultrasound or extracorporeal shock waves may promote nerve regeneration and improve functional outcomes. Because currently clinical data is unavailable, we performed a meta-analysis following the PRISMA-guidelines to investigate the therapeutic effect of ultrasound and shock wave therapies on motor nerve regeneration. Ten ultrasound-studies (N = 445 rats) and three shock-wave studies (N = 110 rats) were identified from multiple databases. We calculated the difference in means or standardized mean difference with 95% confidence intervals for motor function, nerve conduction velocity and histomorphological parameters of treated versus sham or non-treated animals. Ultrasound treatment showed significantly faster nerve conduction, increased axonal regeneration with thicker myelin and improved motor function on sciatic functional index scale (week two: DM[95%CI]: 19,03[13,2 to 25,6], 71 animals; week four: 7,4[5,4 to 9,5], 47 animals). Shock wave induced recovery improvements were temporarily significant. In conclusion, there is significant evidence for low-intensity ultrasound but not for extracorporeal shock wave treatment to improve nerve regeneration. Prospective clinical trials should therefore investigate available FDA-approved ultrasound devices as adjunct postoperative treatment following nerve surgery.